The effect of thyroid substitution therapy on serum lipids in patients with a mild form of subclinical hypothyroidism - Valentina Velkoska-Nakova; Brankica Krstevska; Biljana Todorova; Sasha Jovanovska-Mishevska (Revista Mexicana de Endocrinología, Metabolismo y Nutrición, 2023)
Background: Overt hypothyroidism and severe subclinical hypothyroidism (ScH) are associated with dyslipidemia, and its condition is reversible after levothyroxine therapy (L-T4). Objective: We investigated the differences in lipids between patients with a mild form of ScH and healthy subjects, and the effect of L-T4 on lipid parameters in ScH group. Materials and methods: Fifty-seven patients with newly diagnosed ScH with thyroid-stimulating hormone (TSH) levels below 10 mIU/L and 30 healthy subjects were included in the study. Lipid parameters were evaluated at the first visit in both groups, and after 5 months euthyroid stage in patients with ScH. Results: Average value of TSH in patients with ScH was 8.1 ± 1.9 mIU/L. At the baseline, the ScH patients had a significantly higher total cholesterol, low-density lipoprotein (LDL-C), and non-high-density lipoprotein (non-HDL-C) levels, and lower HDL-C than the control group. Thyroid substitution therapy in the ScH group significantly decreased total cholesterol and LDL-C, and increased HDL-C. TSH positively correlated with total cholesterol (r = 0.147, p < 0.05). The effect of the L-T4 on lipid parameters was more pronounced in patients with positive thyroid antibodies. Conclusion: In a small sample, mild form of ScH is associated with hypercholesterolemia, which is reversible after L-T4 therapy. Large prospective studies should confirm these results.